2021
DOI: 10.1108/jm2-06-2020-0160
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of dividend policy on the sustainability of distressed firms

Abstract: Purpose The paper uses firm level data for the top listed firms in New York exchange stock over the period 2000–2017. The analysis is mainly based on 237 firms that already experienced losses at the end of the fiscal year. The study aims to use the properties of the dynamic panel data, specifically the methodology proposed by Arenllo and Bond (1991), to fulfill the objectives of the paper. Design/methodology/approach This paper focuses on the dividend policy management of the firms when they experience a los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Conspicuously, African firms are forced to undergo a novel competition to face the cryptocurrency market. The study highlighted the importance of firm experience and the internal strategies to have a competitive position in this new market (Montout and Sami 2016;Sami and Abdallah 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Conspicuously, African firms are forced to undergo a novel competition to face the cryptocurrency market. The study highlighted the importance of firm experience and the internal strategies to have a competitive position in this new market (Montout and Sami 2016;Sami and Abdallah 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several research studies conducted during different periods have been conducted to study the relationship between financial distress and dividends [33,26,56,49,6]. Some studies have also been conducted that involves exploring the inverse relationship between the variables, which means impact of dividend policy on financial distress [52,53,41]. However, our focus in the current study is to investigate the association between distress and the payout policy of banks.…”
Section: Financial Distress and Dividend Distributionmentioning
confidence: 99%
“…The authors observed a positive effect of cash dividend on share price at the market and also recommended the organizations to work for increasing the priceearnings ratio. Paying dividends to shareholders not adds to increase their wealth, but also helps to paying organizations to achieve sustainability in the long run (Sami and Abdallah, 2021). A policy with higher dividend payment increases the corporate value significantly (Dang et al, 2021;Gupta & Arora, 2021).…”
Section: Effect Of Dividend Policy and Dpo On Firm Performancementioning
confidence: 99%